Clinical evaluation of a sub-lingual vaccine for prevention of exacerbations in COPD - Nadig, P.D.; Haran, A.; Shetty, M. (Asian Journal of Medical Sciences, 2014)
Background: Lower airway bacterial infection is one of the major cause for exacerbation inCOPD. Multicomponent vaccines derived from the various causative pathogens are shownto prevent the exacerbations. Aims and Objectives: The present study was carried out toevaluate the effi cacy of sublingual vaccine (Ismigen) in preventing the exacerbations inCOPD and to observe its tolerability. Materials and Methods: Twenty four COPD patientsmeeting the eligibility criteria were enrolled in the study. Ismigen was administered once aday sublingually for ten days a month for three consecutive months. They were observed over one year for exacerbations, hospitalisations, respiratory symptoms, lung function tests and adverse reactions. The mean scores of the parameters in the previous year were compared with that of the year following treatment. Students t test and Chi- square test were used for analysis. Results: The mean number of exacerbations reduced from 6.79±3.51 to 2.67±1.90 (p<0.001) and the mean number of hospitalisations from 2.29±1.85 to 0.67±0.87 (p<0.001). There was no significant change in the respiratory symptom score and lung function test. Mild non-serious adverse event was reported by one patient. Conclusion: The results indicated that Ismigen could be an effective and well-tolerated add on therapy in COPD to reduce the frequency and severity of exacerbations. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11634 Asian Journal of Medical Sciences Vol.6(4) 2015 51-54